PENGARUH TARIF PPN 12 % DAN PERSEPSI EFEKTIVITAS KEBIJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA BITUNG - Christine Monica Saren; Nofela Letonaung (JIM : Journal Of International Management, 2026)
This study aims to analyze the effect of the planned 12% Value Added Tax (VAT) rate adjustment as mandated by the Tax Regulation Harmonization Law (UU HPP) and perceptions of policy effectiveness on taxpayer compliance at KPP Pratama Bitung. The research employed a quantitative associative approach with a causal design. Primary data were collected through questionnaires distributed to 30 respondents selected using purposive sampling, consisting of corporate taxpayers and individual taxpayers registered as taxable entrepreneurs (PKP). Data analysis was conducted using classical assumption tests and multiple linear regression with SPSS software. The results indicate that the 12% VAT rate has a positive and significant effect on taxpayer compliance, with a significance value of 0.002 and a t-value of 3.328. Perceived policy effectiveness also has a positive and significant effect, with a significance value of less than 0.001 and a t-value of 4.811. The coefficient of determination (R²) of 0.586 indicates that both independent variables explain 58.6% of the variation in taxpayer compliance.